Peningkatan Kemampuan Guru dalam Memanfaatkan Media Lingkungan Sekolah melalui Bimbingan Berkelanjutan di SD Negeri Lamping 3 Kecamatan Citamiang - Yayan Nuryanti (utile: Jurnal Kependidikan, 2018)
This research uses repeated flow/cycle. There are two cycles in this study, which are divided into Cycles I and Cycle II. The research method used in this school action research is descriptive method with percentage technique. Meanwhile, the research action using continuous guidance model. To determine the success of this research, researchers use indicators of achievement of results, which must be measured to see its success with the system score and percentage. Researchers determine the average target of achieving the average indicator of the lowest grade of 70%, Researchers found that the target indicator achievement of the average value of all components in the first cycle reached 81.57% from the previous only 36.14%. In Cycle II, the target of achievement indicators increased to 96.67%. By achieving and / or even exceeding the target of value achievement indicators, the researcher can conclude that the implementation of continuous guidance can improve the ability of the teacher of SD Negeri Lamping 3 in using the school environment media.